Basal Area and Diameter Increment in Long Term Research Sites in Tropical Forests of India - Rai, S. N. (Indian Forester, 2016)
Estimates of basal area in long term research sites of tropical forests, basal area increment and pattern of mortality in tropical rain forests (TRF) and rate of diameter growth in different forest types is given. estimates of basal area ranged 2 around 43m2/ha in tropical rain forests to around 30-35 m2/ha in moist deciduous forests and around 13 mm2/ha in dry deciduous forests. the rate of basal area increment per year in tropical rain forests for the pioneer species was 5.3%, canopy species 3.22%, middle storey species 2.02% and for under storey species 1.87%. the overall rate of basal area increment was 2.06 % per year in TRFs of western ghats of india. the average rate of diameter increment for species in the western ghat ranged between 3 to 3.5 mm per year.